2020
DOI: 10.1186/s12888-020-02593-1
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of pre-employment and pre-deployment psychological screening for disaster relief workers: a systematic review

Abstract: Background: Individuals who conduct disaster relief work overseas are exposed to a variety of traumatic events that can cause distress and trigger psychological illnesses. Identification of which disaster relief workers may be at risk of experiencing psychological distress or mental health disorders is frequently carried out through preemployment or pre-deployment psychological screening. The primary objective of our review was to assess the evidence for pre-employment and pre-deployment psychological screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 86 publications
2
4
0
Order By: Relevance
“…Contrary to qualitative findings from other studies that highlighted the greater risk of exposure to workplace stressors and adversities among field workers, national, and female staff [ 3 , 16 ], these sociodemographic variables were not statistically significant predictors of exposure to stressors or psychological outcomes in this study. These findings together is consistent with results from a recent systematic review that history of mental disorder is one of the few reliable predictors of psychological distress and disorder in this occupation group [ 37 ]. While unique stressors faced by different demographic groups should be paid attention to, these convergent statistical results may also reflect a generally high level of resilience among these groups.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to qualitative findings from other studies that highlighted the greater risk of exposure to workplace stressors and adversities among field workers, national, and female staff [ 3 , 16 ], these sociodemographic variables were not statistically significant predictors of exposure to stressors or psychological outcomes in this study. These findings together is consistent with results from a recent systematic review that history of mental disorder is one of the few reliable predictors of psychological distress and disorder in this occupation group [ 37 ]. While unique stressors faced by different demographic groups should be paid attention to, these convergent statistical results may also reflect a generally high level of resilience among these groups.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to qualitative ndings from other studies that highlighted the greater risk of exposure to workplace stressors and adversities among eld workers, national, and female staff (3,16), these sociodemographic variables were not statistically signi cant predictors of exposure to stressors or psychological outcomes in this study. These ndings together is consistent with results from a recent systematic review that history of mental disorder is one of the few reliable predictors of psychological distress and disorder in this occupation group (37). While unique stressors faced by different demographic groups should be paid attention to, these convergent statistical results may also re ect a generally high level of resilience among these groups.…”
Section: Discussionsupporting
confidence: 88%
“…If we are to accept our finding that resilience confounds the effects of mental illness symptoms on turnover intentions, then one final policy recommendation that should be taken under consideration by hiring managers within corrections would involve the pre-employment screening of applicants to determine their levels of resilience prior to starting the job. Opie et al (2020) found that when employers used pre-employment screening, sometimes consisting of a battery of questions on resilience to determine whether applicants could successfully confront the dangers of a job, their retention rates drastically increased. Therefore, managerial personnel within corrections may find value in screening applicants at the hiring stage to determine if they have the required levels of resilience to overcome the mental hardships of this line of employment.…”
Section: Discussionmentioning
confidence: 99%